SOCIAL IDENTITIES OF BLACK FEMALES IN ENGLISH LANGUAGE TEXTBOOKS USED IN BRAZIL AND CAMEROON: INTERSECTIONALITIES OF RACE, GENDER, SOCIAL CLASS AND CRITICAL RACIAL LITERACY - Ferreira, Aparecida de Jesus (Revista X, 2019)
This article analyzes how the social identities of black females are represented in English-language textbooks used in Brazil and Cameroon; the intention is to generate reflections on how these social identities are portrayed. This research is linked to my participation in an international research project involving universities in Brazil and Cameroon. In the article I analyze a textbook I collected in Cameroon (Bamenda) and another textbook that is used in Brazil. I address the following: 1) What are the results of studies regarding English-language textbooks, the social identities of black females, and intersectionality with the issues of race, gender and social class in Brazil? 2) What do English-language textbooks used in Brazil and Cameroon reveal about black females and intersectionalities with social class? The reference framework that supports this discussion includes the issues of intersectionality, race, gender and social class (CRENSHAW, 1991), as well as critical racial literacy (SKERRETT, 2011; MOSLEY, 2010, FERREIRA, 2015b). The article concludes that black females are less represented than males in textbooks used in both Brazil and Cameroon. In the case of Brazil, black females are less represented than black and white males, and white females.